Views of Chicago: Picturing the Ruins of the Great Fire - Christina Michelon (University of Minnesota Libraries Publishing, 2021)
By pictorially aligning the ruins of Chicago with those of the ancient civilizations of Europe, especially, these representations offered the potential for the recent past to be reframed as storied history.